2021
DOI: 10.1093/mnras/stab1783
|View full text |Cite
|
Sign up to set email alerts
|

The Pristine survey – XII. Gemini-GRACES chemo-dynamical study of newly discovered extremely metal-poor stars in the Galaxy

Abstract: High-resolution optical spectra of 30 metal-poor stars selected from the Pristine survey are presented, based on observations taken with the Gemini Observatory GRACES spectrograph. Stellar parameters Teff and log g are determined using a Gaia DR2 colour-temperature calibration and surface gravity from the Stefan-Boltzmann equation. GRACES spectra are used to determine chemical abundances (or upper-limits) for 20 elements (Li, O, Na, Mg, K, Ca, Ti, Sc, Cr, Mn, Fe, Ni, Cu, Zn, Y, Zr, Ba, La, Nd, Eu). These stars… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 196 publications
5
33
0
Order By: Relevance
“…Finally, we computed bolometric corrections using a new grid of ATLAS models (Mucciarelli et al, in preparation). Our analysis of 30 similar metal-poor red giants with Gemini/GRACES spectra showed that the typical uncertainties in these stellar parameters are ±100 K in effective temperature and ±0.1 dex in log gravity 12 . We adopt these uncertainties here as well.…”
Section: Spectroscopymentioning
confidence: 75%
See 2 more Smart Citations
“…Finally, we computed bolometric corrections using a new grid of ATLAS models (Mucciarelli et al, in preparation). Our analysis of 30 similar metal-poor red giants with Gemini/GRACES spectra showed that the typical uncertainties in these stellar parameters are ±100 K in effective temperature and ±0.1 dex in log gravity 12 . We adopt these uncertainties here as well.…”
Section: Spectroscopymentioning
confidence: 75%
“…The 2-fibre (object+sky) mode was used, and the data initially reduced using the Gemini "Open-source Pipeline for ESPaDOnS Reduction and Analysis" tool, OPERA 45 . Additional steps were taken to improve the final 1D spectra, including improving the SNR in the overlapping order region by inversely weighing by the noise and improving the continuum normalization using an asymmetric sigma-clipping routine 12 . The full spectral range is ∼4,500 Å to ∼1 micron; however, light below ∼4,800 Å is severely limited by poor transmission through the very long optical fibre.…”
Section: Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, large samples of stars with a chemodynamical characterisation, like the one presented in this paper, can be used to check for possible associations with streams in the halo (e.g. Venn et al 2020;Kielty et al 2021). Along the same lines, it would be of interest to obtain high-resolution observations covering larger wavelength ranges (and spectral features of a wider variety of elements) for the two stars that chemo-dynamically stand out from the others (e.g., Pr_210.7513+12.7744 and Pr_255.8043+10.8443; see § 5) to investigate for possible associations with known structures/accretion events.…”
Section: Discussionmentioning
confidence: 99%
“…Spectroscopic follow-up of EMP star candidates is on-going. These observations are conducted both at medium and high-spectroscopic resolution (Caffau et al 2017;Starkenburg et al 2018;Bonifacio et al 2019;Venn et al 2020;Youakim et al 2017;Aguado et al 2019;Caffau et al 2020;Kielty et al 2021). The detailed chemical analysis of individual stars allows us to address three main threads of open issues related to stellar evolution and galaxy formation: (i) the nature and properties of the first stars, (ii) how and when the different components of the structure of the Milky Way assemble, and, finally, (iii) in the hierarchical galaxy formation paradigm, the mass and the degree of chemical evolution of the dwarf galaxy building blocks.…”
mentioning
confidence: 99%